Assessment of implementation level of County Integrated Development Plan (CIDP) in Kisii County Government, Kenya - Onderi Amos Begi; Dr. Simon Nyakwara (IJRDO - Journal of Social Science and Humanities Research, 2020)
The Constitution of Kenya (2010) has pointed out that devolution is geared towards bringing service delivery closer to the people. However, like all new systems of governance, devolution in Kenya has been marred with a myriad of challenges that has seen a huge outcry over the management of county governments, and Kisii County County Government is no exception. This study was intended to reveals factors affecting the implementation of county integrated plan in Kisii County. The purpose of the study was to carry out an assessment of the challenges that affect implementation of County Integrated Development Plans in Kisii County. The study was based on Resource-Based View Theory. The study was based on the randomized cross-sectional survey design, which the researcher adopts in this study, was associated with exploratory and descriptive studies and aimed at examining several groups of people at one point in time. The study targeted 1500 civil servants who involved, 1470 lower cadre civil servants (LCE)., 10 County Executive Committee Members, 15 County Chief Officers who report to CECs and 33 directorates of the respective functional sections or departments of the Kisii County Government. This yielded a sample size of 179 respondents. The sample size was determined by Magnani, (1997) formula. The researcher adopted questionnaire, interview schedule and a document analysis checklist as appropriate instruments for the study. A self-administered questionnaire containing open-ended and closed questions was used to obtain primary data. The study established that the implementation of CIDP was poor; there was no sufficient allocation of resources and the little received resources were not aligned with strategies. The study established that the county did not have competent and qualified employees and it did not have advanced ICT to support attainment of its objectives. The County did not enhance team work and mentorship leading to wastage of money because of inefficiency or inflexibility. Time was also wasted because of bureaucracy or inflexibility leading to poor performance. Correlation analysis revealed that finances, human resource, good leadership and organization culture positively and significantly influence the implementation of CIDP.